Ophthalmic implications following orbital trauma - Turadagi, Kishorkumar; Bellary, Radhika; Channashetti, Gajanan (International Journal of Research in Medical Sciences, 2024)
Background: To study the epidemiology, clinico-radiological pattern of ocular injuries following orbital trauma. Methods: A cross-sectional study was conducted for a period of 6 months, all the patients attending casualty with the history of orbital injuries were included in the study. Proper history and ophthalmological examination were done. The data were recorded in the form of various parameters like type of injury, time, place and severity of injury, site of injury, and radiological pattern of fracture. Results: Out of 100 patients 68 patients had injuries due to road traffic accidents. Most of the victims were males (86%). The most vulnerable age group was 21-30 year (38%). Majority of the patients had lid laceration (n=43, 43%), followed by periorbital swelling with black eye in 40 patients (40%) and iris prolapse in 1 patient. Out of 40 orbital wall fracture 11 fractures were impure and 29 were pure orbital wall fracture. Most of them were orbital floor fracture and least was roof fracture. Conclusions: Road traffic accidents can result in severe ocular trauma. Victims are usually adult males of productive age group. Frontal impacts during the accidents poses the greatest risk of orbito-facial trauma. Factors like open globe injury and multiple orbital wall fracture usually associated with poor prognosis. Use of helmet and seatbelt may reduce the risk of frontal impact and hence vision threatening ocular trauma.